Characterization of Malaysian velogenic NDV strain AF2240-I genomic sequence: a comparative study - Murulitharan, Kavitha; Yusoff, Khatijah; Omar, Abdul Rahman; Molouki, Aidin (Springer, 2013)
Newcastle disease virus (NDV) strain AF2240 is a viscerotropic velogenic strain that is used as a vaccine challenge virus in Malaysia. The identification of the full length genome will be a crucial platform for further studies of this isolate. In this study, we fully sequenced the genome of a derivative of this strain named AF2240-I. The 15,192 nt long genome contains a 55-nt leader sequence at the 3′ whereas the trailer region consists of 114 nt at the 5′. The intergenic sequences between the NP-P, P-M, M-F, F-HN, and HN-L genes comprise 1, 1, 1, 31, and 47 nt, respectively. The acknowledged cleavage site of fusion protein showed amino acid sequence of 112-R-R-Q-K-R-F-117, which corresponds to those of virulent NDV strains. Phylogenetic analysis of the whole virus genome shows that the strain AF2240-I belongs to genotype VIII and is more closely related to velogenic strains QH1, QH4, Fontana, Largo, and Italienas compared to other strains of NDV. Differences are noticed in the hemagglutinin-neuraminidase (HN) and matrix (M) gene between AF2240 and its derivative AF2240-I. This is the first report of a complete genome sequence of an NDV strain isolated in Malaysia.